MODEL PEMILIHAN MODA DAN POTENSI PENGGUNAAN NON MOTORIZED TRANSPORT PADA MASA PANDEMI COVID-19 DI KOTA TEGAL - Pipit Rusmandani; Riandy Sholeh Setiawan; Nurul Fitriani (Rekayasa Sipil, 2021)
This study aims to (1) determine the factors affecting the mode preference in Tegal, (2) determine the factors affecting the potential use of non-motorized transportation in Tegal, and (3) investigate the relationship model among these factors. PLS Structural Equation Modelling (SEM) method was used. The results revealed (1) socio-economic characteristics (KSE) with vehicle ownership indicators influenced the mode choice level, (2) socio-economic characteristic variables with vehicle ownership indicators, travel intention variable (MP) covering working, shopping, and worship indicators, and self-preservation behaviour variable during the pandemic affected the potential use of non-motorized transport [0.801 KSE; (R2= 0,647)] (3) the relationship model among variables [Socio-economy (KSE), purpose of travel (MP), and self-preservation behaviour (PMD)] was =0,280 KSE+ 0.317 MP-0.175 PMD; (R2=0,2570)